The effect of water temperature on the swimming speed of Nile tilapia (Oreochromis niloticus) using computer vision technique - Sangwan, Puttasong; Yoonpundh, Ruangvit; Taparhudee, Wara (RMUTSB ACADEMIC JOURNAL, 2019)
Computer vision technique using a Tracker program was applied to determine how water temperature affected swimming speed of Nile Tilapia. The experiment was divided into 3 treatments: treatment 1 with low water temperature (20.43±1.12 °C), treatment 2 with normal water temperature (26.72±0.67 °C), and treatment 3 with high water temperature (34.73±1.88 °C). There were three replicates of each treatment. Average weight and total length of the experimental fish were 115.30±13.50 g. and 18.30±8.97 cm. Each treatment examined swimming performance of the fish according to feeding time. This was divided into 5 stages as; 15 min before feeding (S1), from start of feeding-15 min (S2), 16-30 min (S3), 31-45 min (S4), and 46-60 min (S5) after feeding. Swimming speed performance and sprint swimming speed were examined in all stages but average sprint swimming speed was tested only in stage 2. Results showed that S2 and S3 of treatment 2 had the highest average swimming speeds at 4.95±2.38 cm/s and 0.87±0.09 cm/s, respectively which were significantly different (P<0.05) from results in treatments 1 and 3. Average sprint swimming speed (S2) was only observed in treatment 2 at 7.00±4.00 cm/s. Findings indicated that the computer vision technique using a Tracker program was useful for studying fish behaviors.